MIDWIFE KNOWLEDGE IN EARLY DETECTION OF CERVICAL CANCER USING VISUAL INSPECTION WITH ACETIC ACID METHOD - Sari, Deviati Juwita; Lestari, Pudji; Mulawardhana, Pungky (INTERNATIONAL JOURNAL OF MIDWIFERY RESEARCH, 2022)
Knowledge of a midwife in to do VIA examination will influence achievement VIA examination. Study this aim for knowing connection Among education and training status with knowledge midwife in detection early cancer cervix use method Visual inspection with acetic acid (VIA) in Banjarmasin City. Research design this is cross-sectional in 26 Puskesmas in Banjarmasin City March – November 2020 with amount sample as many as 172 respondents, retrieval technique sample use non-probability sampling technique is purposive sampling . Instrument study in the form of questionnaires and reports from the Department of Health. Data analysis is carried out by computerization. A total of 172 respondents obtained part big respondents who have P2B and D3 Midwifery education have knowledge not enough by 61.6% and the majority respondents who have not once follow training have knowledge not enough as much as 67.9%. Statistical test results show no there is connection Among education (p = 0,171) and training status (p = 0,001) with knowledge midwife in detection early cancer cervix with use VIA method. Research results show no there is connection Among education and there connection between training status with knowledge midwife in detection early cancer cervix use VIA method in Banjarmasin City. Training is one the step that becomes consideration in increase performance midwife in detection cancer cervical .